Development of the ionisation signal analysis and the thermometry system for the LUX-ZEPLIN direct dark matter detection experiment - Stevens, A (2021)
There is substantiated astrophysical evidence for a substance known as Dark Matter within the universe, at both galactic and cosmological scales. Despite this evidence, the true nature of Dark Matter remains one of the most profound questions in modern physics. One viable candidate is the Weakly Interacting Massive Particle (WIMP), which could nicely explain the observed measurements. The LUX-ZEPLIN (LZ) detector is searching for WIMP interactions with xenon nuclei, through both scintillation and ionisation signals. It comprises a time-projection chamber filled with 7 tonnes of liquid xenon, situated at the Sanford Underground Research Facility in South Dakota.